Gender Wage Gaps among Aboriginals and non-Aboriginals in the Canadian Labour Market - Farahnakian, Azadeh (Université d'Ottawa | University of Ottawa, 2015)
This paper analyzes the gender wage gap among Aboriginal and non-Aboriginal workers in the Canadian labour market, as well as the wage gap between non-Aboriginal and Aboriginal males and females by using the 2011 National Household Survey. An interesting result is that the gender wage gap among Aboriginals is smaller than the one among non-Aboriginals. The wage gap between non-Aboriginals and Aboriginals is also smaller among females than among males. The Oaxaca decomposition of the gender wage gap shows that women in both groups have higher levels of education and higher returns to education, but this is mitigated by the unexplained part, which results from discrimination and other unobserved factors. The lower level of education of Aboriginal workers plays an important role in explaining the wage gap between non-Aboriginals and Aboriginals.